Empowering the Rural Farming Community: A Case of Community Radio in Jharkhand - V. Madhava Rao,; R.R. Hennon,; Rajashree Padhi,; P. Anuradha, (Journal of Agricultural Extension Management, 2014)
The present paper is an outcome of a detailed study based on Chala Ho Gaon Mein Community Radio initiative of Palamu district of Jharkhand. The study was conducted to understand the impact of the. Initiative upon the rural farming community of the specified region. The objective of the paper is to highlight the role of the government in facilitating the community radio for the empowerment of the rural community of Palamu district of Jharkhand. With the new legislation of the Government of India on Community Radio, Chala Ho Gaon Mein Initiative became a vibrant means of information dissemination, a significant platform for people's participation and a forum for expressing their day to day grievances and resolving it locally. 'Chala Ho Gaon Mein' is a unique experiment in using media technologies, especially radio, for development and empowerment of marginalised, rural communities.